DNA interactions of antitumor trans-[PtCl2(NH3)(quinoline)] - Zákovská, A; Nováková, O; Balcarová, Z; Bierbach, U; Farrell, N; Brabec, V (European journal of biochemistry, 1998)
Recent observations that several trans-platinum complexes exhibit antitumor activity including activity in cisplatin-resistant tumor cells, violates the classical structure/activity relationships of platinum(II) complexes. According to these relationships, only bifunctional platinum(II) complexes with cis-oriented leaving ligands should be therapeutically active. In order to contribute to the understanding of mechanisms underlying the antitumor activity of these new trans-platinum analogs, various biochemical and biophysical methods as well as molecular modeling techniques were employed to study the modifications of DNA by antitumor trans-[PtCl2(NH3)(quinoline)]. The results indicated that trans-[PtCl2(NH3)(quinoline)] coordinated monofunctionally to DNA with a similar rate as transplatin. The overall rate of the rearrangement to bifunctional adducts was also similar to that observed in the case of DNA modification by transplatin, i.e. it was relatively slow (after 48 h approximately 34% adducts remained monofunctional). In contrast to transplatin, however, trans-[PtCl2(NH3)(quinoline)] formed considerably more interstrand cross-links after 48 h (approximately 30%) with a much shorter half-time (approximately 5 h) (approximately 12% for transplatin, t1/2 > 11 h). The results also suggested that the quinoline ligand in all or in a significant fraction of DNA adducts of trans-[PtCl2(NH3)(quinoline)], in which platinum is coordinated to base residues, was well positioned to interact with the duplex. The adducts of trans-[PtCl2(NH3)(quinoline)] terminated in vitro RNA synthesis preferentially at guanine residues. Surprisingly, the type and extent of conformational alterations induced in DNA indicates that trans-[PtCl2(NH3)(quinoline)] behaves in some respects like cisplatin, as indicated by the fact that trans-[PtCl2(NH3)(quinoline)]-modified DNA is recognized by cisplatin-specific antibodies. Models for both monofunctional adducts and bifunctional interstrand cross-links are proposed. Computer-generated AMBER models show that the combination of monofunctional covalent binding and a stacking interaction between quinoline and the DNA bases can produce a kink in the duplex which is strongly suggestive of the directed bend produced by the major cisplatin-DNA adduct (1,2 intrastrand cross-link). Unique DNA adducts of this type formed by trans-[PtCl2(NH3)(quinoline)] may contribute to the antitumor efficacy of this agent.
Keywords: ethidium; Cattle; sekvence nukleotidů; adukty DNA; Fluorescent Dyes; protinádorové látky; Thiourea; skot; molekulární sekvence - údaje; Organoplatinum Compounds; thiomočovina; Organometallic Compounds; Ethidium; Animals; DNA Adducts; zvířata; fluorescenční barviva; DNA; Molecular Sequence Data; Base Sequence; organoplatinové sloučeniny; Antineoplastic Agents; organokovové sloučeniny